The Interaction of Solar Wind with Jupiter’s Magnetosphere - Rodríguez-Gómez, Jenny M. (Current Research Progress in Physical Science Vol. 2, 2024)
This chapter presents the effects of the solar wind on Jupiter’s magnetosphere. Using the Michigan Solar Wind Model (mSWiM) solar wind data propagated to Jupiter from 1997 to 2016. This dataset was used to characterize the solar wind parameters that can affect Jupiter’s magnetosphere. For this purpose, the Interplanetary fast shocks: Forward shocks (FS), Reverse shocks (RS), and solar wind dynamic pressure were obtained and analyzed during the apparent opposition periods. The main finding highlights that the fast forward (FS) shocks were predominant during this period and the solar wind dynamic pressure from FS and RS shocks follows the solar cycles 23 and 24. It shows how solar activity and specifically the solar wind affect planetary magnetosphere dynamics.